2022
DOI: 10.1108/ijsi-07-2022-0101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties, permeability and microstructure of concrete using construction and industrial waste

Abstract: PurposeThe purpose of this research is to evaluate construction and industrial waste materials in concrete using different additives.Design/methodology/approachThe experimental study investigated the effect of waste foundry sand (WFS), waste glass (GW) as partial substituent to natural sand and addition of waste glass fibers (GFs) and silica fume (SF) in natural/construction waste aggregate concrete on mechanical properties, durability and microstructure using.FindingsThe results reveal significant strength en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Surprisingly, no long-term decline in resistance has ever been observed. In actuality, the compressive strength of the concrete sample improves with age and increases with the length of time it has been in existence [32]. In this investigation, there was no proof that older concrete containing superplasticizers lost any strength.…”
Section: Discussionmentioning
confidence: 62%
“…Surprisingly, no long-term decline in resistance has ever been observed. In actuality, the compressive strength of the concrete sample improves with age and increases with the length of time it has been in existence [32]. In this investigation, there was no proof that older concrete containing superplasticizers lost any strength.…”
Section: Discussionmentioning
confidence: 62%
“…Sharma [4] indicated that waste could be classified either as unavoidable (or natural waste) or avoidable. If the cost of waste is higher than the cost to prevent it, it is classified as avoidable waste.…”
Section: Introductionmentioning
confidence: 99%
“…If the cost of waste is higher than the cost to prevent it, it is classified as avoidable waste. If the necessary investment for its reduction is higher than the economy produced, it is classified as unavoidable waste [4]. Wu et al [5] grouped waste from the construction field into inert, non-inert, and hazardous categories.…”
Section: Introductionmentioning
confidence: 99%